2010
DOI: 10.1159/000319546
|View full text |Cite
|
Sign up to set email alerts
|

Sharp-Object-Induced Open-Globe Injuries in Iranian Children Admitted to a Major Tertiary Center: A Prospective Review of 125 Cases

Abstract: Ocular trauma in children can result in catastrophic visual and psychological outcomes both for the child and his/her family. According to the WHO, childhood blindness is one of the major causes of avoidable blindness and so target of the Vision 2020 program. To achieve this program’s goals, it is necessary to explore the epidemiological patterns of ocular trauma in different countries which in its turn could be a valuable means to guide us in developing preventive measures. Our study is a hospital-based prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…The recent studies from different regions all around the world revealed the mean age for ocular injury is between 7-11 years (6,7,(11)(12)(13). The mean age of openglobe injuries in pediatric group was found to be 8 (12,13). The mean age is also 8 in our study, in accord with the results of other studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The recent studies from different regions all around the world revealed the mean age for ocular injury is between 7-11 years (6,7,(11)(12)(13). The mean age of openglobe injuries in pediatric group was found to be 8 (12,13). The mean age is also 8 in our study, in accord with the results of other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Seventy-five percent of the injuries occurred under 11 years, in accord with the studies from Asia. The recent studies from different regions all around the world revealed the mean age for ocular injury is between 7-11 years (6,7,(11)(12)(13). The mean age of openglobe injuries in pediatric group was found to be 8 (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Explosive injury is mostly caused by fireworks during the Chinese New Year festival. According to the World Health Organization, childhood blindness is one of the major types of avoidable blindness 11 . Therefore, it is important to teach safety, especially to children 12 …”
Section: Discussionmentioning
confidence: 99%
“…The ratio of males to females presenting with OGIs ranges from 1.9:1 to 5.1:1,[ 10 13 14 15 16 17 18 19 22 23 25 30 31 36 ] though there is no significant difference across these studies in the incidence of right versus left eye affected. Pediatric OGI cases most frequently are caused by sharp objects such as knives[ 7 15 16 17 18 19 20 21 30 33 39 ] making penetrating injury the most common. [ 14 15 18 22 23 ] The majority of injuries occur at home.…”
Section: Demographics and Nature Of Injurymentioning
confidence: 99%
“…[ 14 15 18 22 23 ] The majority of injuries occur at home. [ 7 16 17 24 29 30 38 40 ] In some developing countries, outdoor and street injuries are more common. [ 13 14 ] Other accidental causes of OGI in children have been documented,[ 41 42 43 44 45 46 47 48 49 ] as well as cases of abuse or assault.…”
Section: Demographics and Nature Of Injurymentioning
confidence: 99%